Politics of Meaning/Meaning of Politics Cultural Sociology of the 2016 U.S. Presidential Election - Mast, Jason L.; Alexander, Jeffrey C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
The 2016 U.S. presidential election revealed a nation deeply divided and in flux. This volume provides urgently needed insights into American politics and culture during this period of uncertainty. The contributions answer the election's key mysteries, such as how contemporary Christian evangelicals identified in the unrepentant candidate Trump a hero to their cause, and how working class and economically struggling Americans saw in the rich and ostentatious candidate a champion of their plight. The chapters explain how irrationality is creeping into political participation, and demonstrate how media developments enabled a phenomenon like "fake news" to influence the election. At this polarized and contentious moment, this volume satisfies the urgent need for works that carefully analyze the forces and tensions tearing at the American social fabric. Simultaneously intellectual and accessible, this volume is designed to illuminate the 2016 U.S. presidential election and its aftermath for academics and students of politics alike. .
Introduction -- Chapter 1: Politics as a Vacation -- Chapter 2: When Voters Are Voting, What Are They Doing?: Symbolic Selection and the 2016 U.S. Presidential Election -- Chapter 3: Deep Stories, Nostalgia Narratives, and Fake News: Storytelling in the Trump Era -- Chapter 4: Journalism after Trump -- Chapter 5: On the Construction Sites of History: Where Did Donald Trump Come From? -- Chapter 6: Donald's Dick: A Man Against the Institutions -- Chapter 7: A Period of "wild and fierce fanaticism": Populism, Theo-Political Militarism, and the Crisis of US Hegemony -- Chapter 8: Raging Against the Enlightenment: Steven Bannon's Anti-Democratic Ideology -- Chapter 9: The Flight 93-ization of American Politics -- Chapter 10: Why Evangelicals Voted for Trump: A Critical Cultural Sociology -- Chapter 11: Muslims as Outsiders, Enemies, and Others: The 2016 Presidential Election and the Politics of Religious Exclusion -- Chapter 12: Populism's Efforts to De-legitimize the Vital Center and the Implications for Liberal Democracy -- Chapter 13: The Fragmenting of the Civil Sphere: How Partisan Identity Shapes the Moral Evaluations of Candidates and Epistemology -- Chapter 14: Legitimacy Troubles and the Performance of Power in the 2016 US Presidential Election -- Afterword.
Keywords: Political sociology; Culture; Sociology; Mass media; America -- Politics and government; Political Sociology; Sociology of Culture; Sociological Theory; Media Sociology; American Politics